Hydrogen: An Endogenous Regulator of Liver Homeostasis - Zhang, Yaxing; Xu, Jingting; Yang, Hongzhi (Frontiers in Pharmacology, 2020)
Basic and clinical studies have shown that hydrogen (H2), the lightest gas in the air, has significant biological effects of anti-oxidation, anti-inflammation and anti-apoptosis. The mammalian cells have no abilities to produce H2 due to lack of the expression of hydrogenase. The endogenous H2 in human body is mainly produced by anaerobic bacteria, such as Firmicutes and Bacteroides, in gut and other organs through the reversible oxidation reaction of 2 H+ + 2 e- ⇌ H2. Supplement of exogenous H2 can improve many kinds of liver injuries, modulate glucose and lipids metabolism in animal models or in human beings. Moreover, hepatic glycogen has strong ability to accumulate H2, thus, among the organs examined, liver has the highest concentration of H2 after supplement of exogenous H2 by various strategies in vivo. The inadequate production of endogenous H2 play essential roles in brain, heart and liver disorders, while enhanced endogenous H2 production may improve hepatic ischemia and reperfusion injuries, hepatitis, and liver regeneration. Therefore, the endogenous H2 may play essential roles in maintaining liver homeostasis.